Patterns of Rural Development: A Cross-Country Comparison Using Microeconomic Data - Winters, Paul; Essam, Timothy; Zezza, Alberto; Davis, Benjamin; Carletto, Calogero (2012)
This article proposes a general pattern of rural development in which increases in per capita income are associated with a decline in the importance of agricultural production and a rise in the importance of non-agricultural income sources. Following the approach to examining Engel's Law, we use data from 15 developing countries and a merged dataset to test whether such a pattern emerges. The analysis shows a strong, positive relationship between per capita income and the share of income earned from rural non-agricultural wage employment and a negative relationship between per capita income and agricultural production.